Researching "On and In" Global South Countries: Southeast Asia - Mohammed, Ilyas (Poligrafi, 2022)
Over the last decade, there has been an increasing awareness that colonialism continues through various overlapping iterations of coloniality, such as politics, economics, security and academia. Academics from global north countries and global south countries have highlighted and called for the dismantling of coloniality in its various iterations. Perhaps the most vocal decolonising calls have come from global north academics wanting to decolonise global north academia in the form of epistemic decolonisation. As such, in this article, I call on global north academics researching 'on and in' global south countries to employ decolonial methodologies to avoid inadvertently reinforcing coloniality. By utilising autoethnography and critical decolonial reflexivity, I offer ways for global north academics researching on or in global south countries to guard against reinforcing coloniality during their research.